Pilgrim Stories : On and Off the Road to Santiago, Journeys Along an Ancient Way in Modern Spain - Frey, Nancy Louise, 1968- (Book collections on Project MUSE., 1998)
Unlike the religiously-oriented pilgrims who visit Marian shrines such as Lourdes, the modern Road of St. James attracts an ecumenical mix of largely wel.